Transport in the Baltic Sea region: Perspectives for the economies in transition - Hans Böhme; Claus-Friedrich Laaser; Henning Sichelschmidt; Rüdiger Soltwedel (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The Baltic Sea region has been subject to processes of both disintegration and integration. On the southeastern shore of the Baltic Sea, former CMEA trade relations as well as the traditional system of Soviet socialist division of labour has disintegrated after 1991. With the exception of the Russian Federation's oblasts of Leningrad and Kaliningrad, the transition economies in the Baltic Sea region have turned to the West and are eager to participate in the process of European integration. Poland and Estonia participate in the negotiations for EU enlargement, sooner or later Latvia and Lithuania will follow suit. Physically, integration is brought about by transport that results from trade and other economic interchange. Hence, trade and further economic development may be hampered by all severe obstacles to transport – in the fields of transport infrastructures, of transport markets, of complementary legal frameworks, or of the daily transport business. In the present study, the authors analyse the current pattern of transport in the Eastern Baltic Sea region with special reference to the economies in transition, and identify and assess the various obstacles to transport in this region. Based on the empirical findings, the study presents economic policy recommendations and shows potential remedies to overcome such obstacles. Although missing infrastructure links and insufficient capacities are easily visible, the authors hold that "software" problems (arising from regulatory regimes, but in particular from administrative procedures) are more pressing than infrastructure deficiencies and should be addressed with urgency.
Keywords: 330; Verkehrsinfrastruktur; Verkehr; Verkehrsökonomik; Übergangswirtschaft; Verkehrspolitik; Ostsee; Polen; Russland; Estland